Computational biologists: moving to the driver's seat. Issue 1 (December 2017) - Yanai, Itai; Chmielnicki, Eva
Abstract The recent shift of computational biologists from bioinformatics service providers to leaders of cutting-edge programs highlights the accompanying cultural and conceptual changes that should be implemented by funding bodies and academic institutions.